Strongest MJO on Record Triggers Extreme Atacama Rainfall and Warmth in Antarctica. Issue 6 (19th March 2019) - Rondanelli, R.; Hatchett, B.; Rutllant, J.; Bozkurt, D.; Garreaud, R.
Abstract: Tropical perturbations have been shown theoretically and observationally to excite long‐range atmospheric responses in the form of Rossby wave teleconnections that result from the equator to pole gradient of planetary vorticity. An extreme teleconnection event occurred during March 2015 in the Southeastern Pacific. As a result, extreme high temperatures were observed in Southwestern South America and the Antarctic Peninsula simultaneously with an extreme rainfall and flood event in the hyperarid Atacama desert. We show that the origin of these seemingly disconnected extreme events can be traced to a Rossby wave response to the strongest Madden‐Julian Oscillation (MJO) on record in the tropical central Pacific. A barotropic wave number 3 to 4 perturbation with group velocity between 15 and 30 m/s is consistent with the trajectory and timing followed by the upper‐level anomalies radiating away from the tropics after the MJO episode. Plain Language Summary: Large atmospheric waves can travel from the tropical regions after being excited by deep convective systems over the oceans. Sometimes this tropical rainfall occurs associated to tropical waves that take from 30 to 60 days to travel around the planet, known as the Madden‐Julian Oscillations. The strongest of such Madden‐Julian wave was observed during March 2015. Here we show that this wave triggered a response that traveled far east and south of the original rainfall heating, producing extreme weather in Antarctica (highest temperature in continental Antarctica observed on record) as well as extreme weather in the Pacific South American coast (major flooding in the Atacama desert). We emphasize that this case illustrates the importance of tropical extremes in setting temperature and precipitation extremes far away from the tropics, including polar regions. This has major consequences for these extreme environments: for the maintenance of the ice shelves in Antarctic Peninsula and for the hyperarid character of the Atacama desert. Key Points: The strongest MJO is connected to extreme high temperature and precipitation in Antarctica and Atacama Wave trajectory from reanalysis agrees with a wave number 3 to 4 Rossby wave propagating from the Central Pacific We emphasize how this extreme event shows the importance of tropical variability on driving extreme weather far away from the tropics